Digital Image Correlation and Finite Element Analysis of Bone Strain Generated by Implant-Retained Cantilever Fixed Prosthesis - Tribst, J. P.M. [UNESP]; Dal Piva, A. M.O. [UNESP]; Bottino, M. A. [UNESP]; Nishioka, R. S. [UNESP]; Borges, A. L.S. [UNESP]; Özcan, M. (My University, 2020)
PURPOSE: The present study evaluated the displacement and strain generated in an implant- supported fixed prosthesis under axial and non-axial loads using two methods. MATERIALS AND METHODS: Three implants were inserted in a resin block. The Digital Image Correlation (DIC) was used to measure displacement and strain generated on the surface of the resin blocks for the different load applications (500N, 1 image/second). A 3-dimensional model was constructed and a load of 500 N was applied at an axial point and a non-axial point through finite element analysis (FEA). RESULTS: Both methods gave similar trends for the strains, and both gave slightly higher strains with non-axial loading. FEA predicted higher strain magnitude (±11%) in comparison with DIC, but with the same mechanical behavior. According to ANOVA, the loading influenced the strain concentration. Higher strain was generated for non-axial loading around the implant nearest to the loading. CONCLUSIONS: For implant-retained cantilever fixed prosthesis, the same load applied in the lever arm induces higher strain in the cervical area of the last implant, which suggests more damaging potential than a load applied at the center of the prosthesis.
Keywords: Biomechanical Complications; Computerized Models; Dental Implant; Finite Element Analysis